Epizootic Activity of Natural Plague Foci in the Territory of the Russian Federation in 2014 and Prognosis for 2015 - N. V. Popov; V. E. Bezsmertny; A. N. Matrosov; T. V. Knyazeva; A. A. Kuznetsov; Yu. M. Fedorov; V. P. Popov; D. B. Verzhutsky; V. M. Korzun; E. V. Chipanin; V. M. Dubyansky; O. V. Maletskaya; et al. (Проблемы особо опасных инфекций, 2015)
. Isolated were 128 plague agent strains: from rodents and lagomorphs - 24, 103 - from bloodsucking arthropods. One strain was obtained from a patient in the territory of Gorno-Altaisk high-mountain natural plague focus. Substantiated has been epizootiological prognosis claiming persistent challenging epidemiological situation in the foci. Outlined is the necessity to use epizootiological forecasting as the basis for scheduling and carrying out epidemiological monitoring and preventive measures in active natural plague foci. Due to the varying epidemiological significance of Y. pestis ssp. pestis , Y. pestis ssp. caucasica , and Y. pestis ssp. altaica strains the data on their spatial distribution should be deployed for differentiation of focal areas according to the degree of the potential epidemic hazard.